HUBUNGAN ANTARA PENGETAHUAN DENGAN PELAKSANAAN KEWAJIBAN ZAKAT BAGI PNS YANG BERAGAMA ISLAM DI UNIVERSITAS NEGERI MAKASSAR - Mustaring, Mustaring; Sudirman, Muh. (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2020)
This study aims to determine the knowledge of zakat, the implementation of zakat, and the relationship between knowledge and the implementation of zakat obligations for civil servants who are Muslim at Makassar State University.The method to be used to achieve the objectives in this study is a qualitative descriptive approach. Through this approach, this research will describe the real situation in detail and actuality. As for the background of the use of this method, because the phenomenon to be studied requires a description or in-depth description and analysis. Thus, answers will be found that can reveal true events or facts on the ground. The results showed that six variations in the level of knowledge of Civil Servants in the Makassar State University environment on the obligation of zakat. The implementation of zakat obligation for Civil Servants in Makassar State University has not been fully implemented well and basically they have a strong awareness and desire to fulfill their obligations. The relationship between knowledge and implementation of zakat obligations for Civil Servants in the Makassar State University environment.